Supply chain security: evaluating RSA vulnerabilities in the era of Shor's algorithm - Galhardi, Antonio Cesar (2024)
This study presents a comparative analysis of algorithms based on Shor's Algorithm, using the ChatGPT artificial intelligence tool for generating codes in Qiskit, a language focused on quantum computing, in two different periods: August 2023 and February 2024. The results revealed a significant improvement in the suggestions provided by the tool, indicating notable progress in strategies for implementing the algorithm. In the most recent analysis, from February 2024, a substantial risk to the security of RSA encryption was identified if automatically generated codes are implemented without supervision in environments with remote access to quantum computers. This risk has critical implications for modern logistics, particularly in the sharing of sensitive information throughout the supply chain, reinforcing the need for robust cybersecurity solutions to mitigate the potential impacts of this technological evolution.